Teachers' attitudes toward the uses of the computers in language teaching at Ha Nam teachers' training college = Thái độ của giáo viên đối với việc sử dụng máy tính trong giảng dạy ngoại ngữ tại trường CĐSP Hà Nam. M.A Thesis Linguistics: 60 14 10 - Nguyễn, Thị Chung (University of Languages and International Studies, 2017)
46 p. + CD-ROM